Manufacturing, mechanical and flame retardant properties of poly(lactic acid) biocomposites based on calcium magnesium phytate and carbon nanotubes. (July 2018) - Yang, Wei; Tawiah, Benjamin; Yu, Chao; Qian, Yi-Fan; Wang, Li-Li; Yuen, Anthony Chun-Yin; Zhu, San-E; Hu, En-Zhu; Chen, Timothy Bo-Yuan; Yu, Bin; Lu, Hong-Dian; Yeoh, Guan Heng; et al.
Graphical abstract: Abstract: A bio-flame retardant, calcium magnesium phytate (CaMg-Ph), was synthesized via the reaction of calcium chloride and magnesium chloride with phytic acid from renewable source. Poly(lactic acid) (PLA) biocomposites were fabricated using CaMg-Ph as a bio-sourced phosphorous additive combined with acid-treated carbon nanotubes (CNT). The thermal, mechanical and flame retardant properties of PLA biocomposites were evaluated by thermogravimetric analysis (TGA), tensile and cone calorimeter tests. The addition of the combinations (19 wt% CaMg-Ph and 1 wt% CNT) into PLA resulted in a slight increase in tensile strength (52.8 MPa), compared to 20 wt% CaMg-Ph (50.4 MPa), indicating the reinforcement effect of the CNT. The addition of 10, 20, and 30 wt% CaMg-Ph led to significant reduction in PHRR by 22%, 33%, and 38% respectively with a similar trend in THR. PLA/CaMg-Ph19/CNT1 showed lower PHRR (35.0%) and higher char yield (18.4 wt%) compared to PLA/CaMg-Ph20, suggesting the preferable flame retardant properties.